Heart rate variability discriminates competitive levels in professional soccer players - Proietti, R.; Di Fronso, S.; Pereira, L. A.; Bortoli, L.; Robazza, C.; Nakamura, F. Y.; Bertollo, M. (The Journal of Strength and Conditioning Research, 2017)
Heart rate variability (HRV) has been increasingly used to monitor team sports athletes. Besides the traditional time domain indices (i.e., the SD of successive RR intervals [SDNN] and the root mean square difference of successive normal RR intervals [RMSSD]), recently the use of the stress score (SS), which is an inverse function of the SD2 index derived from the Poincaré plot, and the sympathetic/parasympathetic ratio (S/PS) to monitor soccer players has been proposed. However, the reliability of these new indices and the ability of HRV to differentiate between soccer competitive levels are unknown. The aim of this study was to analyze the reliability of the different HRV-derived indices in professional soccer players during the competitive period and to compare HRV of professional soccer players from 3 teams of distinct competitive levels (i.e., Italian Second Division [2D], European League [EL], and Champions League [CL]). Fifty-four male professional soccer players from 3 different teams of 2 European countries (Italy and Germany) participated in the study. The intraclass correlation coefficient values of the HRV indices varied from 0.78 (very large) to 0.90 (near perfect). The coefficient of variation (CV) values for RMSSD and SDNN were all <5.00%, although the CV for SS was 6.13% and for S/PS, it was 21.33%. Both the CL and EL groups, assumed to be internationally qualified, presented higher lnRMSSD and lnSDNN and lower lnSS and S/PS than the 2D. Therefore, the HRV can be considered reliable in professional soccer players and is able to differentiate between international- and national-level players.